SIMPLE ESTIMATOR AND CONSISTENT STRONGLY OF STABLE DISTRIBUTIONS - Guevara Otiniano, Cira (2016)
Stable distributions are extensively used to analyze earnings of financial assets, such as exchange rates and stock prices assets. In this paper we propose a simple and strongly consistent estimator for the scale parameter of a symmetric stable Levy distribution. The advantage of this estimator is that your computational time is minimum thus it can be used to initialize intensive computational procedure such as maximum likelihood. With random samples of sized n we testedthe efficacy of these estimators by Monte Carlo method. We also included applications for three data sets.